An Overview and Framework for a Marketing Viewpoint on Digital Business Models - Candraningrat; Niken Savitri Primasari; Zainul Wasik (Journal of Managerial Sciences and Studies, 2024)
The market is being transformed by strong digital developments. To deal with these changes, businesses can use digital business models. The focus of this special issue is digital business models. We discuss their relevance, propose a conceptual framework, and discuss how digital business models affect markets, businesses, and their performance. In this issue, we introduce various papers and show how each fits into the conceptual framework. We discuss four important future research topics.